Case Study of Parenting Patterns in Five Long-House Families in Kampung Air Balikpapan - Nurul Kamaliah Umasangaji; Isradi Zaenal; Arlin Adam; Andi Alim; Muhammad Ichwan Iskandar Alam; Tharia Nurizky Putri (JSPH (Jurnal Sosiologi Pendidikan Humanis), 2023)
It is essential to realize that wrong parenting can lead to serious social problems such as promiscuity, sexual violence against girls, early marriage, neglect, dropping out of school, and drug trafficking and use. This study aims to analyze the parenting style of children of families who live in the longhouse of Kampung Atas Air, Margasari Village, West Balikpapan District, Balikpapan City. The sociological perspective used is critical. This research uses the qualitative method of the case study approach. The research informants were five families living in longhouses consisting of mothers or fathers and children, community leaders, and local government. The results of the study show that the social reality of the longhouse family is not in line with the social order of the local community, such as; promiscuity occurs, children dropping out of school, early marriage, neglect of children and wives, and drug trafficking. The parenting style implemented is permissive and uninvolved parenting. Children are ignored so that they are not controlled in the association. Caring for children is the responsibility of the extended family, not the responsibility of the nuclear family, namely the biological parents, so children receive less attention from their parents during the growth period until adulthood. The research concludes that a parenting style not by the social order causes social disorder.